2018
DOI: 10.1038/s41598-018-22409-3
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin promotes inflammation by enabling binding of self-RNA to cell surface scavenger receptors

Abstract: Under homeostatic conditions the release of self-RNA from dying cells does not promote inflammation. However, following injury or inflammatory skin diseases such as psoriasis and rosacea, expression of the cathelicidin antimicrobial peptide LL37 breaks tolerance to self-nucleic acids and triggers inflammation. Here we report that LL37 enables keratinocytes and macrophages to recognize self-non-coding U1 RNA by facilitating binding to cell surface scavenger receptors that enable recognition by nucleic acid patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 59 publications
4
68
0
Order By: Relevance
“…This enhances production of large amounts of type I IFN, leading to the functional activation of myeloid dendritic cells (mDCs), monocytes, NK cells, keratinocytes, as well as Th1/Th17 differentiation, which further increase the pro-inflammatory, e.g., IFN-γ, IL-22, and IL-17, cytokine expression [120,121]. In line with this, a novel mechanism of nucleic acid recognition by LL-37 utilizing cell surface RNA scavenger receptors (SRs) has been described [122], which results is enhanced clathrin-dependent endocytosis, facilitating the overproduction of inflammatory cytokines and chemokines. Recently also RNase7 was found to utilize plasmacytoid dendritic cell (pDC) TLR-9 signaling mode of IFN-α activation even more strongly than LL-37, emphasizing its crucial role in autoimmune inflammatory skin diseases [123].…”
Section: Molecular Mechanisms Of Anti-and Pro-inflammatory Action Of mentioning
confidence: 87%
“…This enhances production of large amounts of type I IFN, leading to the functional activation of myeloid dendritic cells (mDCs), monocytes, NK cells, keratinocytes, as well as Th1/Th17 differentiation, which further increase the pro-inflammatory, e.g., IFN-γ, IL-22, and IL-17, cytokine expression [120,121]. In line with this, a novel mechanism of nucleic acid recognition by LL-37 utilizing cell surface RNA scavenger receptors (SRs) has been described [122], which results is enhanced clathrin-dependent endocytosis, facilitating the overproduction of inflammatory cytokines and chemokines. Recently also RNase7 was found to utilize plasmacytoid dendritic cell (pDC) TLR-9 signaling mode of IFN-α activation even more strongly than LL-37, emphasizing its crucial role in autoimmune inflammatory skin diseases [123].…”
Section: Molecular Mechanisms Of Anti-and Pro-inflammatory Action Of mentioning
confidence: 87%
“…On the other hand, LL37 promotes the viability, migration, and invasion of malignant melanoma cells through Y‐box binding protein 1 (YB‐1)‐dependent pathways . As a previous report suggested, LL37 binds surface scavenger receptors that enable macrophages to recognise self‐non‐self‐coding U1 RNA . Since the tumor microenvironments of SCC and EMPD possess substantial numbers of CD163+ M2‐polarised TAMs, especially in invasive phenotypes, increased levels of LL37 in invasive phenotypes might stimulate TAMs in SCC and EMPD via scavenger receptors (CD163).…”
Section: Discussionmentioning
confidence: 97%
“…LL37 is an amphipathic cationic peptide that can induce various immunomodulatory functions, including induction of inflammation and anti‐tumor immune responses . On the other hand, LL37 promotes the viability, migration, and invasion of malignant melanoma cells through Y‐box binding protein 1 (YB‐1)‐dependent pathways .…”
Section: Discussionmentioning
confidence: 99%
“…Cell extracts from a UVR-damaged keratinocyte cell line (normal human epidermal keratinocytes [NHEK]) were then shown to upregulate these adhesion molecules in an endothelial cell line (human dermal microvascular endothelial cells [HDMEC]). Since the Gallo group previously discovered that LL-37 bound to self-RNAeactivated keratinocytes and innate immune cells (macrophages) (Takahashi et al, 2018), the authors then used RNAse III to demonstrate that adhesion molecule upregulation required RNA. Finally, the authors determined that LL-37 and a model self-RNA molecule (synthetic snoU1 double-stranded RNA [dsRNA]) could reproduce this phenomenon.…”
Section: Immune Cell Entry Into Rosaceamentioning
confidence: 99%
“…For instance, can this pathway be initiated by UVR damage to any keratinocyte or must damage occur in a keratinocyte near a dermal capillary? Since cathelicidin is normally concentrated in the superficial epidermis (Braff et al, 2005), the diffusion of superficially released LL-37:dsRNA might be impeded by LL-37's intrinsic affinity for cell membranes (Vandamme et al, 2012) or by scavenger receptors on keratinocytes (Takahashi et al, 2018). This paper demonstrated that LL-37 is present throughout rosacea epidermis, so there may be sufficient LL-37 to allow (1) LL-37:dsRNA to traverse the entire epidermis or (2) be available to bind dsRNA released from keratinocytes closer to the dermal-epidermal junction.…”
Section: Questions Arising From This Studymentioning
confidence: 99%